Restoring Epistemic Credibility for Expert Communities in Sub-Saharan Africa - Edmund Terem Ugar; Agemir Bavaresco (Revista de Filosofía, 2023)
In this paper, we engage with Heidi Grasswick’s argument on epistemic distrust as an epistemic value. We show how expert communities have in the past perpetuated epistemic harm to people of colour as recipients of knowledge. We highlight the adverse effects of these harms in our social milieu by limiting our discussion to COVID-19 vaccine hesitancy in sub-Saharan Africa. We then conclude that the scepticism of the COVID-19 vaccines by people of colour within the aforementioned locale can be understood in the context of epistemic distrust. Finally, We show how epistemic credibility toward the expert community, precisely scientific communities, by the non-expert community can be restored.